Sistem Informasi Pemetaan Data Alumni dan Lowongan Kerja (Studi Kasus : SMK Nurul Islam Cianjur) - Uro Abdurohim; Maurien Desiana Effendi; Linda Apriyanti (LPPM STMIK Bandung, 2020)
Today, the development of technology and information is growing rapidly in various aspects of life. One of them is in the academic field, from elementary school to lectures. Nowadays schools have used information technology a lot in their academic management, which makes it easy tomanage related data. Vocational school is a vocational secondary education which has the role to prepare studentsto be ready to enter the workforce. SMK has an institution called the Special Labor Exchange (BKK). Special job fairs are service institutions for the placement of workers in secondary education units and higher education units. The Special Work Exchange is a bridge between SMKs and the industrial world. Cianjur Nurul Islam Vocational School is a private school in the form of a foundation, in this school there is also a Special Work Exchange (BKK) program preferred for alumni of Cianjur Vocational School Nurul Islam students, and also for other schools.